Fasilitas Pendidikan Dan Pelatihan Mode Di Pekanbaru Dengan Pendekatan Arsitektur Kontemporer - Monica, Indah; Hidayat, Wahyu; Susilawati, Mira Dharma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The development and existence of increasing fashion can attract the attention of the people including young people. Pekanbaru becomes the right location for this design because there is no fashion education facility and public interest to fashion so that it is needed a place that accommodates fashion education activity in Pekanbaru. Fashion Education and Training Facility is a place that accommodates the activities to explore the world of fashion and equipment by keeping up with the times from time to time. The development of the fashion world in line with the development of contemporary architecture that is varied and innovative both from the shape and appearance and use of materials that will support the look of contemporary architectural style. This design aims to be able to support the activities of the fashion that is educative. The research methods that is used include field data collection, literature study, and empirical studies. The results of this study is a design of the building with a concept of